The Correlate between Argyrophilic Nucleolar Organizer Region Stain and Ki-67 Immnochistochemistry in Diagnostic Breast Cancer - Hassan ALgarsh (Emergency Department of Hospital San Pedro (Logroño, Spain), 2020)
Introduction: This experimental study gauged the value of argyrophilic nucleolar organizer region (AgNOR) staining as a possible technique for the estimation of cell kinetics in conventional histology sections, in benign and malignant breast lesions. Methods: With a silver staining technique and immunohistochemistry, we associated the numbers of AgNORs and Ki67 scores in 30 breast carcinomas and 10 benign breast lesions. Results: The mean values of Ag NORs silver stain dots count for normal, benign, grade II and III were 1.28±0.17, 2.83±0.68, 5.23±0.87 and 7.32±0.92, respectively. There was a statistically significant difference (p≤0.001) was noticed between the all individual groups, among the normal and breast lesion as well as among the GII and GIII. Immunohistochemical Results of Ki-67 protein exhibited homogenous golden-brown color in control case and a positive brown granules or diffuse dark brown color in the nuclei of both benign and malignant cases under the 400X magnify examined under the light microscope. Discussion: AgNOR counts performed on routine formalin-fixed paraffin sections could provide substantial kinetic evidence. Additionally, the difference in AgNOR counts between benign and malignant tumors is such that they may be of diagnostic worth.